The influence of particle size of amino-functionalized MCM-41 silicas on CO2 adsorption. Issue 43 (27th October 2017) - Gatti, G.; Vittoni, C.; Costenaro, D.; Paul, G.; Mangano, E.; Brandani, S.; Marchese, L.; Bisio, C.
Abstract : The effect of the particle size of hybrid organic–inorganic MCM-41 silicas on the CO2 adsorption properties has been investigated. Abstract : The CO2 adsorption properties of hybrid organic–inorganic MCM-41 silicas with different particle sizes are described here. Micrometric to nanometric MCM-41 silicas are functionalized by introducing amino groups via grafting of 3-[2-(2-aminoethyl)aminoethyl]aminopropyltrimethoxysilane (PAPTS). A combination of FTIR and SS-NMR spectroscopies is adopted to distinguish between physisorbed and chemisorbed CO2 . A higher amount of CO2 is physisorbed in the nanometric sample because of a higher pore volume, whereas chemisorbed (carbamate and acid carbamic) species are more abundant in the micrometric sample. The adsorption process is also quantitatively studied using three different techniques ( i.e. volumetric measurements, Thermo-Gravimetric Analysis (TGA) and Zero Length Column (ZLC) analysis), especially focusing on the reversibility of the reactions between CO2 and amino groups. The three techniques show a higher CO2 adsorption capacity for MCM-41 with nanometric size compared to the micrometric one. Finally, the process is studied at different temperatures ( i.e. from 35 to 90 °C) in order to find the best operating conditions.